The economic analysis of environmental policy and law : an introduction - Faure, Michael; Skogh, Göran (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2003)
This book covers many of the recent advances in the field and attempts to integrate some of the crucial legal and economic instruments which have not yet been subjected to proper analysis.
Includes bibliographical references (p. 325-341) and index.
osc 5/9/16, ijb 19/03/2019
Loans
Keywords: Environmental law --- Economic aspects; Environmental policy--- Economic aspects; Enviromental economics